BILIMLENDIRIWDE ALDÍNǴÍ PEDAGOGIKALÍQ TÁJIRIYBELER, MASHQALALAR, SHESHIMLER - Turımbetov, B. (SCIENCE and SOCIETY, 2021)
This article presents the experience of local teachers in the usage of pedagogical technologies, and some misunderstandings in it. And also given scientifically based recommendations for their correct use and guidance for action.